Diseño de una propuesta de estrategias de posicionamiento orientadas al desarrollo del turismo en las Reservas Ecológicas ubicadas en la parroquia Nanegalito, provincia Pichincha - Oyos Acurio, Daysi Viviana (2015)
This dissertation has the purpose of designing a model of strategic proposals for positioning oriented to the development of tourism in the ecological reserves located in the parish Nanegalito, Pichincha Province. Through the application of research techniques such as: interviews, surveys and direct observation to the residents, tourists and administrators of the ecological reserves. We were able to determine that the residents of the parish they are not related to these tourist places do not have tourist packages to offer and there is no signaling in order to reach these sites of attraction. For that the ecological reserves have a better reception of tourists both domestic and foreign it intends to make strategic alliances with several travel agencies in the that will promote each one of the reservations, improve the infrastructure to provide a better service to the tourists, implement activities of attraction to improve the image of the reservations, train managers and the general public about the care of the environment, customer service, implementing a web page where they are the five ecological reserves to allow them to become more known by tourists and visiting each of these sites. The study that was realized to the ecological reserves put itself to consideration of the managers so that they realize the design implementation strategies for positioning.